Bahasa Using di Desa Serut Kecamatan Panti Kabupaten Jember - Elok Darojatin; Agus Sariono; Hairus Salikin (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This study described the maintenance of Using language in Serut village, Panti, Jember regency and the factors influencing the situation of language maintenance. This study included into the qualitative study. The data in this study were the written and spoken information. This study used ethnographic communication approach which was the data collection works into two steps, they were observation and in-depth interview. The data analysis in this study was divided into three parts: data reduction, data presentation, and pulling the conclusion. The conclusions of this study were the condition of Using language maintenance in Desa Serut, Kecamatan Panti, Kabupaten Jember categorized as high. The older age speaker was, the higher Using language maintenance speaker would be. In contrast, the younger age speaker was, the lower maintenance speaker would be. The speaker in the lower social class has a high Using language maintenance rather than a high social class. The factors that affected it were 1). The force of national language, 2). The inheritance of the language, 3). The interlanguage contact, 4). The interethnic marriage, and 5). The acknowledge of identity.